PENGARUH CUSTOMER EXPERIENCE TERHADAP REVISIT INTENTION PADA PAKET WISATA SEPEDA DI DESA PENGLIPURAN - Ni Wayan Setyaningsih; I Wayan Suardana; LGLK. Dewi (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2020)
Customer experience is one of the strategies created at the moment of truth that has a long-term impact on subsequent visiting decisions. Interest in revisiting in this study is called revisit intention, defined as the possibility of tourists to repeat activities or revisit a tourist attraction. This research was conducted to determine the effect of customer experience to the revisit intention of the domestic tourists of bicycle tour package users